Current Knowledge on the Vascular Effects of Menthol - Silva, Henrique (Frontiers in Physiology, 2020)
Menthol is a monoterpene alcohol, widely used in several food and healthcare products for its particular odor and flavor. For some decades, menthol has been known to act on the vasculature directly in the endothelium and vascular smooth muscle (VSM), with recent studies showing that it also evokes an indirect vascular response via sensory fibers. The mechanisms underlying menthol’s vascular action are complex due to the diversity of cellular targets, to the interplay between signaling pathways and to the variability in terms of response. Menthol can evoke either a perfusion increase or decrease in vivo in different vascular territories, an observation that warrants a critical discussion. Menthol vascular actions in vivo seem to depend on whether the vascular territory under analysis has been directly provoked with menthol or is located deep/distant to the application site. Menthol increases perfusion of directly provoked skin regions due to a complex interplay of increased NO, EDHF and sensory nerve responses. In non-provoked vascular beds menthol reduces vasoconstriction which might be attributed to heat-conservation sympathetically-mediated vasoconstriction, although an increase in tissue evaporative heat loss due the formulation ethanol may also play a role. There is increasing evidence that several of menthol’s cellular targets are involved in cardiovascular diseases, such as hypertension. Thus menthol and pharmacologically-similar drugs can play important preventive and therapeutic roles, which merits its further investigation.